Comparison of microsatellite and SNP DNA markers for pedigree assignment in Black Tiger shrimp, Penaeus monodon. Issue 3 (2nd August 2012) - Sellars, Melony J; Dierens, Leanne; McWilliam, Sean; Little, Bryce; Murphy, Brian; Coman, Greg J; Barendse, William; Henshall, John
Abstract Custom‐built single‐nucleotide‐polymorphism (SNP) marker systems that are compatible with Sequenom® chemistry are compared with a general purpose microsatellite marker system in their ability to accurately assign Black Tiger shrimp parentage. The microsatellite system consisted of 13 markers, while the SNP systems comprised of 63 (SNPa), 59 (SNPb) or 122 markers (SNPab). Comparisons were made using animals from commercial breeding lines with thresholds for assignment derived using simulated genotypes. Pedigree assignment for commercial lines was highest when panel SNPab was used. Panel SNPa, panel SNPb and Msat functioned with an overall similar level of power for pedigree assignment, however, for some families, the Msat panel was not as powerful. Pedigree assignment for the simulated diploid genotypes was higher for all SNP panels compared with Msat. Overall the three SNP panels provided parentage assignment rates suitable for commercial shrimp breeding programs with assignment rates in the simulated genotypes greater than 96.8% and correct assignments greater than 99.3%. Compared with the microsatellite panel, custom‐built SNP panels, whether they operate as single panels, or as a combined panel, have improved power to perform dam and sire assignment to progeny and provide faster turnaround time as they are compatible with Sequenom® chemistry.